Corruption: A many-headed monster - Walt, Barend Johannes van der (Koers, 2001)
The prevalence of corruption poses a serious threat to our nation. This paper intends to investigate, apart from the various forms of corruption and our reactions to them, the causes of and the possible cures for this evil in our society.